A Review on Image Classification Approaches and Techniques - Shivam Modgil , Bobbinpreet Kaur (International Journal of Advanced Science and Technology, 2020)
The article discusses the literature about the different approaches used to identify images based on objects. Classification is a vitally important and complex task in computer vision. Classification is based upon object or item description, texture, or similarity. Classification of images refers to image labelling in one of the predefined groups. Pixels are a measurement unit shown in a picture. Pixel grouping of the picture groups into different classes. Classification of images involves image creation, preprocessing of images and segmentation of images. Many methods of classification were established for the classification of images. This article discusses various methods of classification, such as artificial neural networks (ANN), naive Bayesian (NB), K-nearest neighbor (KNN), decision tree (DT)